Students' Perceptions of Guru Penggerak at Senior High School 1 Palembang - Aziza, Nur; Azzahra, Anisah; Lestari, Septia Sri; Oviyanti, Fitri; Maryamah, Maryamah (FKIP - Universitas Riau, 2025)
This study explores students' perceptions of the implementation of the Guru Penggerak role at SMA Negeri 1 Palembang, a program initiated by the Ministry of Education and Culture to enhance learning quality through transformative leadership. Using a descriptive quantitative approach, 150 purposively selected students participated as respondents. Data were collected through structured questionnaires and analyzed with descriptive statistics and correlation tests. The findings reveal that most students have positive perceptions, particularly regarding learning innovation, communication, and inclusive leadership. However, perceptions vary depending on students’ involvement in programs led by the Guru Penggerak. This study's novelty lies in examining how educational innovation and school culture dynamics influence students' perceptions, an area rarely explored in the local context. The results provide valuable insights for policymakers to optimize the Guru Penggerak program in fostering inclusive and collaborative learning environments. Additionally, the findings offer practical implications for designing teacher training programs tailored to student needs.